Probenecid-Blocked Pannexin-1 Channel Protects Against Early Brain Injury via Inhibiting Neuronal AIM2 Inflammasome Activation After Subarachnoid Hemorrhage - Zheng, Yonghe; Tang, Wenwen; Zeng, Hanhai; Peng, Yucong; Yu, Xiaobo; Yan, Feng; Cao, Shenglong (Frontiers in Neurology, 2022)
Aim: Previous studies have proved that inhibiting inflammasome activation provide neuroprotection against early brain injury (EBI) after subarachnoid hemorrhage (SAH) which is mainly focused on microglial inflammatory response, but the potential role of neuronal inflammasome activation in EBI have not been clearly identified. This study examined whether the pannexin 1 channel inhibitor probenecid could reduce EBI after SAH by inhibiting neuronal AIM2 inflammasome activation. Methods: There are in vivo and in vitro parts in this study. Firstly, adult male SD rats were subjected to the endovascular perforation mode of SAH. The time course of pannexin-1 and AIM2 expressions were determined after SAH in 72 hours. Brain water content, neurological function, AIM2 inflammasome activation and inflammatory response were evaluated at 24 h after SAH in sham, SAH group and SAH+Probenecid group. In the in vitro part, HT22 cell treated with hemin was applied to mimic SAH. The expression of AIM2 inflammasome was detected by immunofluorescence staining. Neuronal death and mitochondrial dysfunction were determined by LDH assay kit and JC-1 staining. Results: The pannexin-1 and AIM2 protein levels were upregulated after SAH. Pannexin-1 channel inhibitor probenecid attenuated brain edema and improved neurological dysfunction by reducing AIM2 inflammasome activation and ROS generation after SAH in rat. Treating HT22 cell with hemin for 12 hours resulted in AIM2 and caspase-1 upregulation, and increased mitochondrial dysfunction and neuronal cell death. Probenecid significantly attenuated the hemin-induced AIM2 inflammasome activation and neuronal death. Conclusions: AIM2 inflammasome is activated in neuron after SAH. Pharmacological inhibition of pannexin-1 channel by probenecid attenuated SAH-induced AIM2 inflammasome activation and EBI in vivo and hemin-induced AIM2 inflammasome activation and neuronal death in vitro.